Crushing characteristics of aluminum/CFRP/aluminum hybrid tubes prepared by spinning forming. (1st October 2020) - Han, Zhengdong; Li, Huaguan; Xu, Xiaocun; Wang, Hao; Li, Hongli; Tao, Jie
Abstract: The aluminum/carbon fiber reinforced plastics (CFRP)/aluminum hybrid tube (H-III) with a good interface bonding was prepared by spinning forming to explore its crushing behaviors and energy absorption mechanism. The quasi-static crushing test was conducted to analyze the crashworthiness. Wrapped hybrid tube (H-I) and assembling aluminum/CFRP/aluminum hybrid tube (H-II) were involved for comparative purpose. The results showed that H-III tube outperformed all hybrid structures in crashworthiness and possessed 20.5% higher energy absorption than the summation of the individual components. Good bonding interaction between CFRP/metal interface obtained by spinning forming promoted the extra restriction from outer aluminum tube on the CFRP layer, which significantly improved the crashworthiness. Delamination failure behavior in CFRP/metal interface was numerically investigated. Moreover, the deformation modes of each layer in H-III hybrid structure comparing with corresponding single structure were explored. It was found that the development of delamination failure during crushing was bound to contribute to the improvement of energy absorption. The aluminum tubes in the single structure exhibited concertina mode while diamond mode dominated those in the hybrid structure under the bonding interaction. The more adequate damaged CFRP layer was identified in the hybrid structure than the single structure, making more contribution to energy absorption.